1990
DOI: 10.1111/j.1476-5381.1990.tb12053.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerosolised substance P on lung resistance in guinea‐pigs: a comparison between inhibition of neutral endopeptidase and angiotensin‐converting enzyme

Abstract: 1We have examined in guinea-pigs, in vivo, the effects of inhibition of neutral endopeptidase (NEP) and angiotensin-converting enzyme (ACE) on the airway response to aerosolised substance P (SP). We aerosolised captopril (4.6mM, 60 breaths; 210nmol) to inhibit ACE and acetorphan (0.3, 1 and 3mM, 60 breaths; 9nmol, 33nmol and 110nmol respectively) to inhibit NEP. We also examined the effect of the highest dose of acetorphan (110 nmol) on the response to aerosolised acetylcholine (ACh).2 Responsiveness to SP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Pretreatment with the NEP24.11-inhibitor phosphoramidon, also given by the inhaled route, caused a pronounced potentiation of the increase in lung resistance induced by inhaled NKA, as well as a small but significant potentiation of airway microvascular leakage in intrapulmonary airways. We found similar effects with inhaled SP, confirming a previous study showing potentiation of the bronchoconstrictor response to SP by another NEP24.1 1-inhibitor, acetorphan (Lotvall et al, 1990b). In addition, we found that inhaled NKA was more potent than SP in increasing RL whereas inhaled SP was more potent than NKA for induction of airway microvascular leakage, which is consistent with previous studies in which these tachykinins were administered by the i.v.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Pretreatment with the NEP24.11-inhibitor phosphoramidon, also given by the inhaled route, caused a pronounced potentiation of the increase in lung resistance induced by inhaled NKA, as well as a small but significant potentiation of airway microvascular leakage in intrapulmonary airways. We found similar effects with inhaled SP, confirming a previous study showing potentiation of the bronchoconstrictor response to SP by another NEP24.1 1-inhibitor, acetorphan (Lotvall et al, 1990b). In addition, we found that inhaled NKA was more potent than SP in increasing RL whereas inhaled SP was more potent than NKA for induction of airway microvascular leakage, which is consistent with previous studies in which these tachykinins were administered by the i.v.…”
Section: Discussionsupporting
confidence: 82%
“…In several studies the bronchoconstrictor response induced by inhaled SP has been shown to be potentiated by inhibition of this enzyme (Dusser et al, 1988;Lotvall et al, 1990b), and a leftward shift of a dose-response curve of up to 2 log units has been observed (Lotvall et al, 1990a). In the present study we have shown that inhibition of NEP24.11 also leads to a potentiation of the bronchoconstrictor response to inhaled NKA to a similar degree.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Both ACE and NEP inhibitors potentiate SPinduced bronchoconstriction in vitro (Sekizawa et al, 1987a,b) and in vivo (Shore et al, 1988), presumably by preventing the degradation of SP. However, when SP is given by inhalation to guinea-pigs, while its effect is potentiated by an inhaled NEP inhibitor, inhaled captopril has no effect (Lotvall et al, 1990) suggesting that NEP but not ACE is important in degrading SP delivered from the airway. For BK, captopril and phosphoramidon are equally effective which argues that inhibition of degradation of tachykinins released from sensory nerves by instilled BK cannot be the sole explanation for their effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that the physiological effects of the neuropeptides are regulated by their enzymatic degradation in the pulmonary microenvironment (7)(8)(9)(10)(11)(15)(16)(17). When SP is presented to the airway surface, its action is regulated predominantly by the activity ofNEP, while the physiological effects of VIP are regulated by NEP and a tryptic enzyme.…”
Section: Discussionmentioning
confidence: 99%